Tuning of terahertz resonances of pyridyl benzamide derivatives by electronegative atom substitution - Dash, Jyotirmayee (Journal of Infrared, Millimeter, and Terahertz Waves, 2018)
N-(pyridin-2-yl) benzamide (Ph2AP)-based organic molecules with prominent terahertz (THz) signatures (less than 5 THz) have been synthesized. The THz resonances are tuned by substituting the most electronegative atom, fluorine, at ortho (2F-Ph2AP), meta (3F-Ph2AP), and para (4F-Ph2AP) positions in a Ph2AP molecule. Substitution of fluorine helps in varying the charge distribution of the atoms forming hydrogen bond and hence strength of the hydrogen bond is varied which helps in tuning the THz resonances. The tuning of lower THz resonances of 2F-Ph2AP, 3F-Ph2AP, and 4F-Ph2AP has been explained in terms of compliance constant (relaxed force constant). Four-molecule cluster simulations have been carried out using Gaussian09 software to calculate the compliance constant of the hydrogen bonds. Crystal structure simulations of the above molecules using CRYSTAL14 software have been carried out to understand the origin of THz resonances. It has been observed that THz resonances are shifted to higher frequencies with stronger hydrogen bonds. The study shows that 3F-Ph2AP and 4F-Ph2AP have higher hydrogen bond strength and hence the THz resonances originating due to stretching of intermolecular hydrogen bonds have been shifted to higher frequencies compared to 2F-Ph2AP. The methodology presented here will help in designing novel organic molecules by substituting various electronegative atoms in order to achieve prominent THz resonances.
Keywords: Compliance constant; Density functional theory; Ph2AP molecule; Terahertz spectroscopy